Multilayers formed by polyelectrolyte-surfactant and related mixtures at the air-water interface - Li, P; Penfold, J; Thomas, RK; Xu, H (Elsevier, 2019)
The structure and occurrence of multilayered adsorption at the air-water interface of surfactants in combination with other oppositely charged species is reviewed. The main species that trigger multilayer formation are multiply charged metal, oligo- and polyions. The structures vary from the attachment of one or two more or less complete surfactant bilayers to the initial surfactant monolayer at the air-water interface to the attachment of a greater number of bilayers with a more defective structure. The majority of the wide range of observations of such structures have been made using neutron reflectometry. The possible mechanisms for the attraction of surfactant bilayers to an air-water interface are discussed and particular attention is given to the question of whether these structures are true equilibrium structures.